Study of the Distribution of Interstellar Dust in the Milky Way Using Gaia DR3 (2025)
Accurately characterizing interstellar dust in the Milky Way is key to correcting distortions in astronomical observations and to understanding galaxy formation and evolution. This work presents a new three-dimensional map of dust extinction in the disk and adjacent regions of our Galaxy, constructed from measurements in the third Gaia data release (GDR3). We perform a detailed analysis of the distribution of stars, extinction, and reddening across a radial range of 10 kpc and a vertical extent of ±2 kpc (upper and lower regions). From the data analysis, we select sources with reliable distance estimates, thus providing a robust basis for characterizing the dust distribution. Using height (z) binning and robust statistics (median and extinction contrast), we analyse a large stellar sample to reveal the vertical and radial behaviour of the dust. Our results confirm known components such as the thin and thick disks and show that the stellar distribution follows the expected exponentially decaying profile; the stellar disk, when considered without type-dependent biases, is approximately symmetric. By contrast, the dust disk (traced by extinction A)exhibits a marked asymmetry: the vertical structure in the northern Galactic hemisphere differs from that in the southern hemisphere at all radii. We compute various profiles of stellar density and extinction across different z layers to identify regions where stellar and dust structures coexist. Finally, we produced maps of stellar and dust structures with DisPerSE and analysed their correlations, identifying features such as the Perseus and Centaurus arms and several star clusters. Our results are consistent with prior work and provide a calibrated, reliable map of dust in the Milky Way.